Immigration - LaShelle, Frank Elmer (My University, 1899)
Introduction: The subject of immigration is one that has but lately assumed gigantic importance in America; but as we shall see, has long been stubborn and knotty problem for the older nations. Owing to certain natural and Political conditions, it is only when these natural conditions are vanishing and these political ones becoming modified that we fund this vast question thrust upon us and a demand is felt for a solution of the problem before it goes beyond the controlling line. In treating this question, I desire to take up first, a fit of history closely connected with the United States, and to consider the political, economical, moral, and social effects, and try if possible to offer a partial solution to this great question. Immigration and emigration are said to be the phenomena of modern life. As early as we have a record, it is an undisputed fact that men will change their location with the attending good or bad results.
Citation: LaShelle, Frank Elmer. Immigration. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Immigration; Historical Conditions; Colenization; Emigration; Theses; Manuscripts (documents)